EKSISTENSI KARYA SENI RUPA POTRET AGUS SUWAGE TAHUN 1995 - 2009 - Much. Sofwan Zarkasi (Pascasarjana Institut Seni Indonesia Surakarta, 2010)
This research entitled â€œExistence of Portrait Fine Arts by Agus Suwage in 1995-2009â€ by Much Sofwan Zarkasi was proposed to know and describe existence of portrait fine arts by Agus Suwage in 1995-2009 that included its birth, aesthetic, and effect for fine arts development in Indonesia. This research used criticism for holistic arts approach which presented three components as information source like artist as source of genetic information, work art as source of objective information and audience as source of affective information. This research resulted in: first, portrait fine arts by Agus Suwage in 1995-2009 were born from process of social and symbolic interaction that Agus Suwage passed. His portrait as subject matter in his portrait fine arts has been solution for seeking form which represented his interest and response to humanity topic freely and intimately according to his personal meaning. Then his portrait fine arts has been developed his popularity in fine arts field, either national or international. Second, portrait fine arts by Agus Suwage in 1995-2009 provided a dynamic fine arts aesthetic with self-portrait and idol figure as his subject matter. Aesthetic in portrait fine arts by Agus Suwage in 1995-2009 was influenced indirectly by his academic experience at graphic design program which is full of symbolic form, structured text and composition represented his idea and personality. This aesthetic as representation of Agus Suwage's personality differenced his portrait fine arts with others. Third, portrait fine arts by Agus Suwage in 1995-2009 brought portrait theme to be popular theme indirectly into contemporary fine arts development in Indonesia, especially intimately visual object among artists, work arts and environment. Portrait fine arts by Agus Suwage in 1995-2009 generated new trend about work arts creation. This trend used self-portrait continuously in fine arts creation in Indonesia.Keywords: birth, aesthetic, and effect.